Significance of tumor-associated neutrophils, lymphocytes, and neutrophil-to-lymphocyte ratio in non-invasive and invasive bladder urothelial carcinoma - Wael Abdo Hassan; Ahmed Kamal ElBanna; Noha Noufal; Mohamed El-Assmy; Hany Lotfy; Rehab Ibrahim Ali (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Background Tumor-infiltrating neutrophils and lymphocytes play essential roles in promoting or combating various neoplasms. This study aimed to investigate the association between tumor-infiltrating neutrophils and lymphocytes and the neutrophil-to-lymphocyte ratio in the progression of urothelial carcinoma. Methods A total of 106 patients diagnosed with urothelial carcinoma were was. Pathological examination for tumor grade and stage and for tumor-infiltrating neutrophils, both CD4 and CD8+ T lymphocytes, as well as the neutrophil-to-lymphocyte ratio were evaluated. Results The presence of neutrophils and the neutrophil-to-lymphocyte ratio correlated with high-grade urothelial neoplasms. In both low- and high-grade tumors, the lymphocytes increased during progression from a non-invasive neoplasm to an early-invasive neoplasm. CD8+ T lymphocytes increased in low-grade non-muscle-invasive tumors compared to non-invasive tumors. Additionally, there was a significant decrease in CD8+ T lymphocytes during progression to muscle-invasive tumors. Conclusions Our results suggest that tumor-infiltrating neutrophils and CD8+ T lymphocytes have a significant effect on tumor grade and progression.